Determinants of Entrepreneurial Intention: A Study on Indonesian Students - Satriadi, Satriadi; Almaududi Ausat, Abu Muna; Heryadi, D. Yadi; Widjaja, Warkianto; Sari, Ade Risna (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2022)
Finding jobs for university graduates is becoming more difficult as the number of job opportunities available is not proportional to the number of graduates. This situation is aggravated by the low interest of the Indonesian population in entrepreneurship, which is at roughly 3.1%. This study aims to investigate the effect of entrepreneurial self-efficacy, creativity, attitude toward entrepreneurship, social media, entrepreneurial culture, and motivation on student’s entrepreneurial intentions. Social media is warranted in the study as the respondents are in the group of millennials. A quantitative method was used. The data analysis employed Structural Equation Modelling (SEM) with Partial Least Squares (PLS). The participants were undergraduate students from universities in Malang City and Surabaya, Indonesia, recruited using an online questionnaire. The research sample included 315 respondents. This study used self-efficacy, creativity, attitude, culture, and motivation as the determinants of student’s entrepreneurial intention. It proposed six hypotheses that reflect the impact of each determinant on entrepreneurial intentions. The study revealed that of the six hypotheses tested, all had a significant impact on explaining the determinants of student’s entrepreneurial intention. Social media is proven to be the catalyst for student entrepreneurial intention. Educated students recognize and assume that social media can help run a business without requiring a large investment. This study also suggests that lecturers' involvement enables students to acquire entrepreneurial skills in classroom learning and organizations. Thus, students with a greater level of entrepreneurial insight will find it easier to foster an entrepreneurial attitude and think more imaginatively to commercialize new ideas in the form of product development before they realize their entrepreneurial potential.